2020
DOI: 10.2147/tacg.s207491
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Importance of Small Non-Coding RNAs in Human Reproduction: A Review Article</p>

Abstract: Background: MicroRNAs (miRNA) play a key role in the regulation of gene expression through the translational suppression and control of post-transcriptional modifications. Aim: Previous studies demonstrated that miRNAs conduct the pathways involved in human reproduction including maintenance of primordial germ cells (PGCs), spermatogenesis, oocyte maturation, folliculogenesis and corpus luteum function. The association of miRNA expression with infertility, polycystic ovary syndrome (PCOS), premature ovarian fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“…Maternal age is another major factor for infertility. In a study, various differentially expressed miRNAs were expressed in women above the age of 40s compared to women in their 20s and miR-93 was exceptionally expressed only in blastocytes with chromosomal abnormalities in older women (57), this is a clear indication that maternal ageing is not only a risk factor for infertility but also associated with modification of miRNAs profiles (58).…”
Section: Mirnas and Fertility In Pcosmentioning
confidence: 99%
“…Maternal age is another major factor for infertility. In a study, various differentially expressed miRNAs were expressed in women above the age of 40s compared to women in their 20s and miR-93 was exceptionally expressed only in blastocytes with chromosomal abnormalities in older women (57), this is a clear indication that maternal ageing is not only a risk factor for infertility but also associated with modification of miRNAs profiles (58).…”
Section: Mirnas and Fertility In Pcosmentioning
confidence: 99%
“…The pre‐miRNA is exported from the nucleus to the cytoplasm via Exportin 5, and it is cleaved by Dicer1, a cytoplasmic RNase III. Dicer1 and Argonaute proteins make the RNA‐induced silencing complex (RISC), which is responsible for mature miRNA formation, and the guided strand of miRNA is loaded on RISC (Kamalidehghan et al., 2020; Ni et al., 2011; Sharma et al., 2018).…”
Section: Epigenetic Factors Affecting Sperm Maturationmentioning
confidence: 99%
“…miRNAs can control their target gene expression by antisense base‐paring with mRNAs, a result of which is suppression of mRNA translation and mRNA degradation (Kamalidehghan et al., 2020; Ni et al., 2011; Sharma et al., 2018). miRNAs participate in male reproductive functions at several stages, including gametogenesis, sperm maturation and fertilisation.…”
Section: Epigenetic Factors Affecting Sperm Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen different miRNAs have already been identified in endometrial samples of patients, with repeated implantation failures that presumably regulate the expression of 3800 genes and which were not found in the group of healthy women. It was also shown that ten miRNAs are overexpressed in endometrial samples in women with repeated implantation failures, including miR-23b, miR -199a, and miR-145 [37].…”
mentioning
confidence: 98%